Cold Stress and Nitrogen Deficiency Affected Protein Expression of Psychrotrophic Dyadobacter psychrophilus B2 and Pseudomonas jessenii MP1 - Suyal, Deep C.; Kumar, Saurabh; Yadav, Amit; Shouche, Yogesh; Goel, Reeta (Frontiers in Microbiology, 2017)
Nitrogen (N) deficiency and low temperature conditions are the prominent facet of Western Himalayan agro-ecosystems. A slight change in the environment alters the protein expression of the microorganisms. Therefore, proteomes of the two psychrotrophs Dyadobacter psychrophilus B2 and Pseudomonas jessenii MP1 were analyzed using two dimensional electrophoresis and MALDI–TOF–MS, to determine the physiological response of altitudinally different but indigenous microorganisms in response to cold stress under N depleting conditions. Functional assessment of 150 differentially expressed proteins from both the psychrotrophs revealed several mechanisms might be involved in cold stress adaptation, protein synthesis/modifications, energy metabolism, cell growth/maintenance etc. In both the proteomes, abundance of the proteins related to energy production and stress were significantly increased while, proteins related to biosynthesis and energy consuming processes decreased. ATP synthase subunit alpha, beta, ATP-dependent Clp protease, Enolase, groL HtpG and N(2)-fixation sustaining protein CowN proteins were found to be expressed in both B2 and MP1, similarly to previously studied diazotrophs under low temperature N2 fixing conditions and therefore, can be considered as a biomarker for monitoring the nitrogen fixation in cold niches. Nevertheless, in both the diazotrophs, a good fraction of the proteins were related to hypothetical proteins which are still uncharacterized, thereby, suggesting the need for indepth studies on cold adapted diazotrophs and their adaptive mechanisms.